Analisis keanekaragaman vegetasi di hutan lindung resort pemangkuan hutan Selorejo Kecamatan Dau Kabupaten Malang: Analysys of vegetation diversity in protected forest Selorejo forest support resort, Dau district, Malang regency - Ridlo, M. Tanthowi Qodrir; Hayati, Ari; Prasetyo, Hamdani Dwi (FMIPA UNISMA, 2023)
Forest damage has an effect on ecological functions, such as the root system of forest trees will be disturbed, forest floor covering plants cannot increase soil stability, so they are unable to reduce the speed of water flow which causes erosion and flooding. In general, the presence of vegetation in an area has a positive impact, but the effect varies depending on the structure and composition of the vegetation that grows in the area. This study aims to calculate and analyze the structure, composition and diversity of vegetation in the Selorejo RPH protected forest. This research was conducted from March 6 to July 20, 2022 using survey methods and quadratic transects. The results showed that the composition of vegetation in the protected forest of RPH Selorejo contained 4829 individuals from 64 species belonging to 26 families. At the tree level, the highest INP value was found in the Trembesi species (Samanea saman) with an INP of 169.92%. At the pole level, the highest INP value was found in the Kepuh species (Sterculia foetida) with an INP of 141.05%. At the sapling level, the highest INP value is found in the type of Arabica Coffee (Coffea arabica) with an INP of 70.40%. At the seedling level there are only 2 species, namely; Avocado (Persea americana) and Arabica Coffee (Coffea arabia) with an INP of 0.00% each and at the lower plant level The highest INP value was found in the Tekelan (Ageratina riparia Regel) species with an INP of 63.17%. The diversity index in the protected forest of Selorejo RPH for tree and seedling species was categorized as low diversity, while for saplings, poles and understored species, it was categorized as moderate diversity. Keywords: Forest Damage, Vegetation Analysis, Vegetation Diversity ABSTRAK Kerusakan hutan memberikan pengaruh terhadap fungsi ekologis, seperti sistem perakaran pada pohon hutan akan terganggu, tumbuhan penutup lantai hutan tidak dapat meningkatkan stabilitas tanah, sehingga tidak mampu mengurangi kecepatan aliran air yang menyebabkan erosi dan banjir. Secara umum kehadiran vegetasi pada suatu area memberikan dampak positif, tetapi pengaruhnya bervariasi tergantung pada struktur dan komposisi vegetasi yang tumbuh pada daerah tersebut. Penelitian ini bertujuan untuk menghitung dan mengalisis struktur, komposisi dan keanekaragmanÂ vegetasi di hutan lindung RPHÂ Selorejo. Penelitian ini dilaksanakan pada 6 Maret sampaiÂ 20 Juli 2022 dengan menggunakan metode survey dan transek kuadrat. Hasil penelitian menunjukkan Komposisi Vegetasi di hutan lindung RPH Selorejo terdapat 4829 individu dari 64 spesies yang tergolong ke dalam 26 familia. Pada tingkat pohon Nilai INP tertinggi terdapat pada jenis Trembesi (Samanea saman). Pada tingkat tiang nilai INP tertinggi terdapat pada jenis Kepuh (Sterculia foetida) . Pada tingkat pancang Nilai INP tertinggi terdapat pada jenis Kopi Arabika (Coffea arabica). Pada tingkat semai hanya terdapat 2 spesies yaitu ; Persea americana dan Coffea arabica. serta pada tingkat tumbuhan bawah Nilai INP tertinggi terdapat pada jenis Tekelan (Ageratina riparia Regel). Indeks keanekaragamanÂ di hutan lindung RPH Selorejo pada jenis pohon dan semai dikategorikan keanekaragaman rendah, sedangkan untuk jenis pancang, tiang dan tumbuhan bawah dikategorikan keanekaragaman sedang. Kata kunci: Kerusakan Hutan, Analisis Vegetasi, Keanekaragaman Vegetasi